Analysis of Food Allergen Labeling Regulations on Consumer Safety in Zimbabwe - Bulawayo, Harare (International Journal of Food Sciences, 2023)
Purpose: The aim of the study was to investigate analysis of food allergen labeling regulations on consumer safety in Zimbabwe Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study addresses the significance of food allergen concerns for consumers and food business operators in Zimbabwe. It acknowledges the adoption of the Codex Alimentarius standard (NL 206) for allergen labeling in the country. However, it highlights a research gap in understanding the knowledge and practices of consumers and FBOs regarding food allergies and labeling. The study aims to conduct surveys in Harare, analyzing compliance with NL 206 for local and imported packaged foods. The goal is to provide insights and recommendations for improving food allergen labeling, consumer safety, and awareness in Zimbabwe. Unique Contribution to Theory, Practice and Policy: Health Belief Model (HBM), Theory of Planned Behavior (TPB) & Diffusion of Innovations Theory may be used to anchor future studies on analysis of food allergen labeling regulations on consumer safety in Zimbabwe. Invest in comprehensive consumer education and awareness campaigns to empower individuals to make safe food choices, contributing to enhanced food safety in practice. Work towards global harmonization of allergen labeling standards as a policy measure to simplify compliance for manufacturers and ensure consistent allergen identification on food labels.